Traffic Intersections Noise Levels and Daily Noise Exposure in Chandrapur City, Central India - Rahul K. Kamble (Indonesian Journal of Environmental Management and Sustainability, 2019)
Noise level monitoring was carried out at nine important traffic intersections of the Chandrapur city to ascertain noise levels and daily noise exposure. A pre-calibrated mini sound level meter was used for noise measurement. Observations were recorded for 24 hours and noise level during the day, night and for 24-hours was computed. Maximum noise level during daytime was 84.27 dB(A) at Bangali camp square; whereas, minimum 79.23 dB(A) at Priyadarshani square. In case of nighttime maximum 85.90 dB(A) was at Warora naka square and minimum 70.06 dB(A) at the Jatpura gate. Minimum noise level during 24-hours was at Bagla square 84.34 dB(A) and maximum 91.14 dB(A) at Warora naka square. Noise level during day and night were above the Indian noise standard for the commercial area. The Bangali camp square was identified as the most ear-splitting square during daytime and Warora naka square at nighttime and for 24-hours also. Peak noise was recorded from 10.00 am to 11.00 am and 3.00 pm to 7.00 pm. Vehicular noise, horns, and improper road design contributed significantly to noise levels at traffic intersections. Daily noise exposure analysis by Health and Safety Executive, UK software revealed Bangali camp square and Ramnagar police station square’s daily noise exposure for 0.25 hour was maximum 70 LEP,d and minimum at Gandhi square and Bagla square 65 LEP,d. Noise levels indicated no immediate effect for hearing loss. Control measures for reduction of noise levels at traffic intersections have also been proposed.